Hop on the Story Truck = Kahani Truck Per Sawar - Rumana Husain; Illustrated by Priya Kuriyan (Karachi Oxford University Press, 2015)
Sonia and Anya set off on a journey in a truck through Pakistan. Accompanied by other children, the trip promises to be interesting with the sharing of folktales from different regions.
Include Illustrations.
Keywords: Short English Stories -- Short Urdu Subtitles Stories -- Short Stories -- Pakistan Oxford Books